Structural change commanded by trade opening. The case of Mexican economy - Cardero, María Elena; Aroche, Fidel (Estudios Económicos de El Colegio de México, 2008)
Using Input Output analysis and a special methodology to measure import and export composition the authors make an analysis of the impact of trade liberalization in Mexico. Results seem far away from what was forecasted at the beginning of the 90’s. Exports surge were accompanied by similar imports rates of growth and the import substitution model moved to an import export model. Input Output analysis showed a structural disintegration of the former productive sector. Employment performance was very poor and most of the new jobs created by the export productive sector were built outside the national boundaries.